Plant-Mediated Silencing of the Whitefly Bemisia tabaci Cyclophilin B and Heat Shock Protein 70 Impairs Insect Development and Virus Transmission - Kanakala, Surapathrudu; Kontsedalov, Svetlana; Lebedev, Galina; Ghanim, Murad (Frontiers in Physiology, 2019)
The whitefly B. tabaci is a global pest and transmits extremely important plant viruses especially begomoviruses, that cause substantial crop losses. B. tabaci is one of the top invasive species worldwide and have developed resistance to all major pesticide classes. One of the promising alternative ways for controlling this pest is studying its genetic makeup for identifying specific target proteins which are critical for its development and ability to transmit viruses. Tomato yellow leaf curl virus (TYLCV) is the most economically important and well-studied begomovirus transmitted by B. tabaci, in a persistent-circulative manner. Recently, we reported that B. tabaci Cyclophilin B (CypB) and heat shock protein 70 proteins (hsp 70) interact and co-localize with TYLCV in the whitefly midgut, on the virus transmission pathway, and that both proteins have a significant role in virus transmission. Here we extended the previous work and used the Tobacco rattle virus (TRV) plant-mediated RNA silencing system for knocking down both genes and testing the effect of their silencing on whitefly viability and virus transmission. Portions of these two genes were cloned into TRV constructs and tomato plants were infected and used for whitefly feeding and transmission experiments. Following whitefly feeding on TRV-plants, the expression levels of cypB and hsp70 in adult B. tabaci significantly decreased over 72 h feeding period. The knockdown in the expression of both genes was further shown in the first generation of silenced whiteflies, where phenotypic abnormalities in the adult, wing, nymph and bacteriosomes development and structure were observed. Additionally, high mortality rates that reached more than 80% among nymphs and adults were obtained. Finally, silenced whitefly adults with both genes showed decreased ability to transmit TYLCV under lab conditions. Our results suggest that plant-mediated silencing of both cypB and hsp70 have profound effects on whitefly development and its ability to transmit TYLCV.